LOCAL ADMINISTRATIVE ORGANIZATION REGULATION BY PARLIAMENT THROUGH THE INTERPELLATION OF MEMBER OF THE HOUSE OF REPRESENTATIVES - Kayanha, Aroon (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
The objectives of this research were to 1) explore the interpellation of member of the House of Representatives regarding the operation of Bangkok Metropolitan Administrations during B.E. 2562-2564 2) study the operational guidelines of Bangkok Metropolitan Administrations from interpellation answer of executive (cabinet) and 3) study the Bangkok Metropolitan Administrations performance according to designated guidelines. By using qualitative research approach, using structure interview to collect data, and then analyzing the descriptive data. The results of the research were as follow: interpellation of member of the House of Representatives regarding the operation problems of Bangkok Metropolitan Administrations during B.E. 2562-2564, found that there are only a small portion of all interpellations. While the operational guidelines clarity of Bangkok Metropolitan Administrations depends on rules, orders or administrative acts, and the guidelines from the answers of the executive (Cabinet) has been adapted as a guideline for operations due to the answers of the executive affect the performance of the administrative. The Bangkok Metropolitan Administrations performance according to the assigned guidelines mostly follow rules and orders through adjustments to action plans or some agencies may create a manual to guide their operation.